How Multinational Companies Entrust Digital Applications in Upgrading Employees' Human Resources - Sri Mulyono (Co-Value : Jurnal Ekonomi, Koperasi & Kewirausahaan, 2021)
Background: The problem of International Human Resources management is inseparable from cultural factors. Due to the cultural differences of each country, it is necessary to adjust the differences with modernization solutions and changing patterns of technological solutions. The purpose of the study: Finally, we set the goal of this study to gain a new understanding of how and why international HR can be solved with digital applications Research method: We have analyzed with the help of the Google translation application if there are difficulties in understanding terms and content, then examine the data and evaluation and conclude based on valid and reliable information accuracy. Because we found this data from the results of previous studies, we say our study is secondary data following experts' opinions. Then we also process this study as a qualitative and descriptive study. The results of the study: digital technology can convince companies to train their HR; among others, companies can easily prepare their HR upgrades when they apply their digital technology applications. Furthermore, technology also has an essential role in implementing and corporate human resources training, including international companies. Digital has also been proven to be able to transform human resources for international companies. Our findings hope that they will become essential inputs and contributions for further studies and corporate policy issues Conclusion: we come to our conclusion that the understanding that we get from the study of many papers published in well-known journals is that the purpose of our study has been obtained, which, among other things, we conclude that digital applications can increase the human resources of international companies because digital applications are indeed an essential element so that companies can easily believe in its superiority.